1974
DOI: 10.1111/j.1752-1688.1974.tb00569.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF DIURON ON BACTERIAL POPULATIONS IN AQUATIC ENVIRONMENTS1

Abstract: The naturally occurring, aerobic, heterotrophic bacterial populations of two impounded ecosystems were studied in a laboratory tank system. One reservoir received runoff from a rural drainage basin only, while the second received treated municipal sewage, industrial waste and heavy recreational use. Water from each reservoir was treated with 1.4 ppm final concentration of diuron and studied for total bacterial counts and nutritional source types. Control tanks were studied concurrently. Total counts increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…They also observed an increase in bacterial counts as the result of paraquat (a member of the same chemical family as diquat) addition. Guthrie, Cherry, and Ferebee (1974) reported that diuron (1.4 mg/l) changed the natural bacterial population balance in lake aquatic systems. Some members of the population were inhibited and others possibly were stimulated by diuron.…”
Section: Discuss 10nmentioning
confidence: 99%
See 2 more Smart Citations
“…They also observed an increase in bacterial counts as the result of paraquat (a member of the same chemical family as diquat) addition. Guthrie, Cherry, and Ferebee (1974) reported that diuron (1.4 mg/l) changed the natural bacterial population balance in lake aquatic systems. Some members of the population were inhibited and others possibly were stimulated by diuron.…”
Section: Discuss 10nmentioning
confidence: 99%
“…Future studies should attempt to identify the types of bacteria that survive and/or undergo selective enrichment. Although Guthrie, Cherry, and Ferebee (1974) observed that diuron persisted during a test period of 28 days, the possible degradation of it and other herbicides used in aquatic weed control should be established.…”
Section: Discuss 10nmentioning
confidence: 99%
See 1 more Smart Citation